College Students Understanding on Spectroscopy Topic Using STAD Cooperative Learning Combined with Moodle - Ade Trisnawati; Surjani Wonorahardjo; Munzil Arief (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: Spectroscopy is an abstract and difficult topic in chemistry. Students should be able to explain this concept. The purpose of this pre-experimental research was to explore the understanding of students about spectroscopy using STAD cooperative learning combined with Moodle. A sample of this study were 34 fifth-semester college students majoring at Chemistry studying at the University X. The results showed the students’ understanding on tools instrumentation and their functions on Raman spectroscopy, photometric titration method, the function of the components in IR spectrophotometer, compounds based on transition-absorbing electrons, and the basic principle of atomic spectroscopy material were low.Key Words: students’ understanding of spectroscopy concept, STAD cooperative learning, moodleAbstrak: Spektroskopi merupakan salah satu materi yang bersifat abstrak dan sulit. Mahasiswa harus mampu menjelaskan konsep tersebut dengan baik. Penelitian pra-eksperimental ini bertujuan untuk menggali pemahaman materi spektroskopi mahasiswa pada pembelajaran kooperatif STAD yang dipadu dengan Moodle. Sampel penelitian adalah mahasiswa program Pendidikan Kimia Universitas X semester 5 yang berjumlah 34 mahasiswa. Hasil penelitian menunjukkan bahwa pemahaman mahasiswa pada alat-alat instrumentasi pada spektroskopi Raman beserta fungsinya, metode titrasi fotometrik, fungsi komponen-komponen dalam spektrofotometer IR, macam-macam senyawa penyerap berdasarkan transisi elektronnya, dan prinsip dasar materi spektroskopi atom tergolong rendah.Kata kunci: pemahaman mahasiswa pada materi spektroskopi, pembelajaran kooperatif STAD, moodle